Gray's anatomy - Gray, Henry, 1825-1861.; Churchill Livingstone (London : Harcourt Brace, 1995)
(Producer) Contains the entire contents of the text as well as compu terized animations that show the development of human anatomy at every stage. Illustrated with photographs, line drawings, and state-of-the-ar t cross-sectional images.
Title from disc label.
Copyright date on guide: 1998.
Keywords: Anatomy